Hypocotyl adventitious root organogenesis differs from lateral root development - Verstraeten, Inge; Schotte, Sébastien; Geelen, Danny (Frontiers in Plant Science, 2014)
Wound-induced adventitious root (AR) formation is a requirement for plant survival upon root damage inflicted by pathogen attack, but also during the regeneration of plant stem cuttings for clonal propagation of elite plant varieties. Yet, adventitious rooting also takes place without wounding. This happens for example in etiolated Arabidopsis thaliana hypocotyls, in which AR initiate upon de-etiolation or in tomato seedlings, in which AR initiate upon flooding or high water availability. In the hypocotyl AR originate from a cell layer reminiscent to the pericycle in the primary root (PR) and the initiated AR share histological and developmental characteristics with lateral roots (LR). In contrast to the PR however, the hypocotyl is a determinate structure with an established final number of cells. This points to differences between the induction of hypocotyl AR and LR on the PR, as the latter grows indeterminately. The induction of AR on the hypocotyl takes place in environmental conditions that differ from those that control LR formation. Hence, AR formation depends on differentially regulated gene products. Similarly to AR induction in stem cuttings, the capacity to induce hypocotyl AR is genotype-dependent and the plant growth regulator auxin is a key regulator controlling the rooting response. The hormones cytokinins, ethylene, jasmonic acid and strigolactones in general reduce the root-inducing capacity. The involvement of this many regulators indicates that a tight control and fine-tuning of the initiation and emergence of AR exists. Recently, several genetic factors, specific to hypocotyl adventitious rooting in Arabidopsis thaliana, have been uncovered. These factors reveal a dedicated signaling network that drives AR formation in the Arabidopsis hypocotyl. Here we provide an overview of the environmental and genetic factors controlling hypocotyl-born AR and we summarize how AR formation and the regulating factors of this organogenesis are distinct from LR